Diabetes Education in Children and Adolescents with Type 1 Diabetes in China - Xiaochun Chen; Yangli Dai; Yan Zheng; Ting Yuan; Guanping Dong; Wei Wu; Ke Huang; Jinna Yuan; Junfen Fu; Xuefeng Chen (Tehran University of Medical Sciences, 2022)
Background: The prevalence of Type 1 Diabetes is increasing in pediatrics and diabetes education plays one of the most important role in the management of diabetes, especially in children. However, the related evidence concerned diabetes education is rare in children and adolescents. Therefore, we aimed to investigate the status of diabetes education in hospital, which could help us know the reality of diabetes education. Methods: We choose a nurse who is mainly responsible for diabetes education and management in each hospital to fill out the questionnaire. Overall, 98 nurses were enrolled from tertiary children's specialized hospitals and pediatric wards of general tertiary hospitals from Jan 2018 to Dec 2019. Results: Of 98 nurses enrolled, 61 (63.3%) nurses from 98 hospitals responded, 39 (63.9%) of them received specialized training in diabetes. There were no differences in education characteristics among regions of China. There were 26(42.6%) hospitals have a full-time nurse for diabetes education or nurses with endocrinology training increased with the number of cases/year (P=0.02 and P=0.009). The use of game-based education, knowledge assessment at discharge did not vary among hospital volumes, and the presence of a psychiatrist (P=0.41, P=0.65, and P=0.85, respectively). Diet management education is the most common (23.0%) difficulty in children diabetes education. Conclusion: The level of diabetes education in children and adolescents varied among hospitals, but not among regions in China. There was a lack of resources provided for children and adolescents diabetes education in terms of training and specialized services.